Credit as a strategy for rural development: credit union Mixta Plan Puebla - Guevara Cruz, Juana; Almeraya Quintero, S. Xochilt; Guajardo Hernández, Lenin G. (Revista Mexicana de Ciencias Agrícolas, 2018)
The financing through the credit allows to increase the productive activities of the farmers and the opportunities of access to the market, their income and in this way to improve the quality of life of the families. The objective of this paper was to analyze the distribution of credits made by the Credit Union ‘Mixta Plan Puebla’ (UCMPP) from 1993 to 2005, with the purpose of knowing if these have been destined to the less developed municipalities where its area of greatest dispersion and if the loans granted were tracked. To achieve this purpose, a field investigation was carried out that consisted of the application of 86 surveys to the partners, as well as the preparation of a historical database of the municipalities. Within the results, it is observed that 61% of the credits are distributed in urban communities, while 39% in rural communities, of which 56% are of medium marginalization and 59% of low migration.
Keywords: index of human development; marginalization; migration; rurality